Lightweight pumice mortars for repair of historic buildings –Assessment of physical parameters, engineering properties and durability - Pavlík, Zbyšek; Vyšvařil, Martin; Pavlíková, Milena; Bayer, Patrik; Pivák, Adam; Rovnaníková, Pavla; Záleská, Martina (Construction & building materials, 2023)
[Display omitted] •Lightweight mortars for repair of historical masonry were designed and tested.•Silica sand was partially/fully replaced by crushed pumice of a similar grain size.•The lightweight mortars met the technical requirements for remediation mortars.•The heritage conservation requirements for compatibility were also met.•Mechanical resistant, durable, vapor permeable and thermal insulation mortars. The subject of the presented research was an experimental analysis of physical, engineering and durability parameters of lightweight mortars intended for the repair of historical buildings. Compatibility criteria, the requirements of technical standards and guidelines, and last but not least, previously published research results dealing with the development of mortars for repair delicate historic structures were taken into account in the design of mortar composition. Crushed pumice of a similar grain size was used to lighten the reference lime-based mortar and natural hydraulic lime mortar with quartz filler. Replacement of quartz sand with pumice was 25, 50, 75 and 100% by volume. The use of pumice allowed the fundamental physical, mechanical, hygric, thermal and durability parameters of the lightweight mortars to be such that they met the standard requirements for repair mortars and the heritage conservation requirements for compatibility with the original materials of historic masonry. The main finding was the fact that by replacing sand with pumice, a significant increase in the porosity of the mortars was achieved, while maintaining sufficient mechanical strength due to the pozzolanic reaction of the pumice. Mortars based on natural hydraulic lime have become more resistant to frost and salt crystallization. The advantage of the developed mortars was their low thermal conductivity and high water vapor permeability, which made them suitable for use on damp masonry, which is a substantial scientific contribution of the manuscript.